Box-ticking and Olympic high jumping – Physicians' perceptions and acceptance of national physician validation systems. (2nd September 2018) - Sehlbach, Carolin; Govaerts, Marjan J. B.; Mitchell, Sharon; Rohde, Gernot G. U.; Smeenk, Frank W. J. M.; Driessen, Erik W.
Abstract: Purpose: National physician validation systems aim to ensure lifelong learning through periodic appraisals of physicians' competence. Their effectiveness is determined by physicians' acceptance of and commitment to the system. This study, therefore, sought to explore physicians' perceptions and self-reported acceptance of validation across three different physician validation systems in Europe. Materials and methods: Using a constructivist grounded-theory approach, we conducted semi-structured interviews with 32 respiratory specialists from three countries with markedly different validation systems: Germany, which has a mandatory, credit-based system oriented to continuing professional development; Denmark, with mandatory annual dialogs and ensuing, non-compulsory activities; and the UK, with a mandatory, portfolio-based revalidation system. We analyzed interview data with a view to identifying factors influencing physicians' perceptions and acceptance. Results: Factors that influenced acceptance were the assessment's authenticity and alignment of its requirements with clinical practice, physicians' beliefs about learning, perceived autonomy, and organizational support. Conclusions: Users' acceptance levels determine any system's effectiveness. To support lifelong learning effectively, national physician validation systems must be carefully designed and integrated into daily practice. Involving physicians in their design may render systems more authentic and improve alignment between individual ambitions and the systems' goals, thereby promoting acceptance.